Uso de óleo de girassol ozonizado como adjuvante na cicatrização de lesão cutânea em hamster sírio (mesocricetus auratus) - relato de caso. - Almeida, Glícia Fernanda Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Knowledge of the most efficient methods for wound healing is essential in the medicine of wild and exotic animals, as it allows less time for clinical management of these animals and, consequently, less stress. The breeding of hamsters has become increasingly popular, especially due to the ease of breeding, the value and the characteristics of these animals: they are small, silent, and do not need a large space to live. Because of this ease of handling, some people end up acquiring another animal of the same species and placing both in the same enclosure. In some cases, this sharing of enclosures can generate fights, since hamsters are extremely territorial animals, which can result in significant injuries. The present report refers to the topical adjuvant treatment of a skin lesion using ozonated sunflower oil. Following the 23 days of treatment, granulation tissue formation was observed until the total healing of the lesion
Monografia
Keywords: Cicatrização; Mersocricetus auratus; Ozonioterapia; Roedores; Healing; Mesocricetus auratus; Ozonetherapy; Rodents; CIENCIAS AGRARIAS::MEDICINA VETERINARIA